The distribution of mechanoreceptors in the periodontal ligament of the mandibular canine tooth of the cat. - Cash, R M (1982)
1. Periodontal mechanoreceptor activity has been recorded from fibres in the inferior alveolar nerve. 2. A method has been developed for punctate and electrical stimulation of the periodontal ligament mechanoreceptors through a thin layer of bone overlying the labial aspect of the left mandibular canine tooth root. 3. The distribution of periodontal mechanoreceptors in the labial aspect of the left mandibular canine tooth has been described. 4. All receptors located responded maximally when that part of the ligament in which they lay was in tension. 5. It is suggested that there may be only one type of mechanoreceptor and that the rate of adaptation is dependent on the location of the receptor within the periodontal tissues.